Observations on the miraxonal attraction exercised by sexually immature or adult Biomphalaria glabrata infected or not by Schistosoma mansoni Observações sobre a atração miraxonal exercida por Biomphalaria glabrata infantil e adulta, infectada ou não por Schistosoma mansoni - Luiz Augusto Magalhães; Eliana Maria Zanotti-Magalhães; José Ferreira de Carvalho (Universidade de São Paulo, 1997)
OBJECTIVE: The influence of age and the presence of secondary sporocysts in the miraxonal attraction exercised by Biomphalaria glabrata on miracidia of Schistosoma mansoni of the BH strain were studied. MATERIAL AND METHOD: A glass apparatus containing two compartments joined by a tube and previously tested in other experiments, was used. Specimens of B. glabrata or its snail conditioned water (SCW) selected before the first oviposition (sexually immature), after the first oviposition (adult), with or without secondary sporocysts, were used to attract the miracidia. RESULTS: It was noted that snails or their SCW containing secondary sporocysts lost the ability to attract miracidia. The sexual maturity of the snail did not influence miraxonal attraction. OBJETIVO: Estudou-se a influência da idade e da presença de esporocistos secundários na atração miraxonal exercida por Biomphalaria glabrata sobre miracídios de Schistosoma mansoni da linhagem BH. MATERIAL E MÉTODO: Utilizou-se um aparato de vidro composto de duas câmaras unidas por um canal, previamente testado em outros experimentos. Como atraentes utilizaram-se exemplares de B. glabrata ou a água de condicionamento destes moluscos (SCW) com idade inferior à primeira oviposição (infantil) e com idade superior à primeira oviposição (adulta), contendo ou não esporocistos secundários. RESULTADOS: Verificou-se que os moluscos (ou sua SCW) que continham esporocistos secundários perderam o poder de atrair miracídios. A condição dos moluscos serem infantis ou adultos não interferiu na atração miraxonal.